Effects of extra irradiation on surface and bulk properties of PMPC‐grafted cross‐linked polyethylene. Issue 1 (16th July 2015) - Yamane, Shihori; Kyomoto, Masayuki; Moro, Toru; Watanabe, Kenichi; Hashimoto, Masami; Takatori, Yoshio; Tanaka, Sakae; Ishihara, Kazuhiko
Abstract: Sterilization using high‐energy irradiation is an important aspect of implementing an ultra‐high molecular weight polyethylene acetabular liner in total hip arthroplasty (THA). In this study, we evaluate the effects of extra irradiations such as gamma‐ray or plasma irradiation during sterilization of the poly(2‐methacryloyloxyethyl phosphorylcholine [MPC]) (PMPC) surface and cross‐linked polyethylene (CLPE) substrate of a PMPC‐grafted CLPE acetabular liner. The PMPC‐grafted surface yielded high wettability and low friction properties regardless of the extra irradiations as compared with untreated CLPE. During a hip simulator test, wear resistance of the PMPC‐grafted CLPE liner was maintained after extra irradiation, which is due to the high wettability characteristics of the PMPC surface. In particular, the PMPC‐grafted CLPE liner treated with plasma irradiation showed greater wettability and wear resistance than that with gamma‐ray irradiation. However, we could not clearly observe the changes in chemical properties and morphology of the PMPC surface after both extra irradiations. The physical and mechanical properties attributed to CLPE substrate performance were also unchanged. In contrast, PMPC‐grafted CLPE treated with plasma irradiation showed improved oxidation resistance as compared to that treated with gamma‐ray irradiation after accelerated aging. Thus, we conclude that PMPC‐grafted CLPE with plasma irradiation has promise as a lifelong solution for bearing in THA. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 37–47, 2016.